Diagnostic Approach to Synovial Sarcoma of the Head and Neck Illustrated by Two Cases Arising in the Face and Oral Cavity - Primali Rukmal Jayasooriya; Lindumini Nayanahari Madawalagamage; Balapuwaduge Ranjit Rigorbert Nihal Mendis; Tommaso Lombardi (MDPI AG, 2016)
In the head and neck region, synovial sarcomas (SS) are rare tumours. We describe the diagnostic approach to SS based on two cases which developed in a 26-year-old male in the face and in a 53-year-old female on the alveolar mucosa of the upper jaw. The demographic profile of the patients was compatible with the literature. Histopathologically, both tumours presented as unencapsulated spindle cell tumours arranged into short fascicles. Although the chromosomal translocation of t(X;18)(p11.2;q11.2), transducin-like enhancer of split 1 (TLE-1) and SMARCB1 antibodies derived from gene expression studies are considered as the most sensitive makers to diagnose SS, these facilities were not available. Therefore, our cases were diagnosed as monophasic fibrous SS, utilizing a panel of immunohistochemical markers, including cytokeratins, EMA, Bcl-2, and CD99 as positive indicators and CD34, SMA, MYO-D, and S-100 as negative indicators. PAS staining was used to identify glycogen and to exclude spindle cell carcinomas and leiomyosarcoma, while Alcian blue was used to identify myxoid ground substance and to exclude nodular fasciitis. In conclusion, SS, although rare, should be included in the differential diagnosis of spindle cell tumours of the face and oral mucosa.